Legal Protection of Famous Foreign Brands on Goods with Brand Dilution Which are Sold and Buyed in E-Commerce - Laidy, Yenny; Pakpahan, Kartina; Batubara, Sonya Airini (IJBLE Scientific Publications Community Inc., 2024)
dilution carried out by unscrupulous sellers of a product or brand on an e-commerce platform by utilizing a foreign brand that is already well-known is a form of violation of intellectual property rights by utilizing a well-known foreign brand to increase profits from product sales that are carried out by brand dilution other than that. This is a form of fraud or lying to consumers so that consumers think as if the product they are purchasing is a brand or part of a foreign brand that has undergone brand dilution. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being studied. The data source used is secondary data with quantitative data analysis. The results of this research are that the legal status of well-known foreign brands in Indonesia is recognized as brands that were previously registered and have legal standing, which in the Trademark Law has priority rights to register brands in Indonesia. Indonesia's legal policy regarding the dilution of foreign brands traded on e-commerce has not been specifically regulated in the Trademark Law, but in order to protect well-known foreign brands from brand dilution, Indonesia can use International Intellectual Property Legal Instruments through the Paris Convention, Madrid Protocol